Analisis Kadar Asam Urat pada Penderita Hipertensi dan dengan Penyakit Penyerta - Resehan, Roys; Urip, Urip; Tatontos, Erin Yustin (Poltekkes Kemenkes Palembang, 2025)
Uric acid is the final product of purine metabolism, and its levels in the blood are influenced by its synthesis and excretion. An increase in uric acid levels in the blood, or hyperuricemia, has long been associated with various pathological conditions, including hypertension. Hypertension itself is a major risk factor for cardiovascular and kidney diseases.